2017
DOI: 10.1097/jsm.0000000000000367
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical Outcome Between Athletes and Nonathletes Undergoing Hip Arthroscopy for Femoroacetabular Impingement

Abstract: Although arthroscopic FAI correction and labral preservation surgery is generally beneficial, it appears to provide a better clinical outcome in athletes than in nonathletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 40 publications
3
42
0
Order By: Relevance
“…There is a paucity of literature on female athletes’ postoperative outcomes compared with their nonathletic female counterparts. Murata and colleagues 36 compared a cohort of athletes (47 patients) with a cohort of nonathletes (27 patients), which included both women and men in both groups, and reported that the mean Non-Arthritic Hip Score was superior in the athlete group at all postoperative time points and that the mHHS was superior in the athlete group only at 2 years postoperatively. These results are in agreement with those of the current study suggesting that female athletes have superior postoperative outcome scores at a minimum of 2 years postoperatively when compared with their nonathlete counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of literature on female athletes’ postoperative outcomes compared with their nonathletic female counterparts. Murata and colleagues 36 compared a cohort of athletes (47 patients) with a cohort of nonathletes (27 patients), which included both women and men in both groups, and reported that the mean Non-Arthritic Hip Score was superior in the athlete group at all postoperative time points and that the mHHS was superior in the athlete group only at 2 years postoperatively. These results are in agreement with those of the current study suggesting that female athletes have superior postoperative outcome scores at a minimum of 2 years postoperatively when compared with their nonathlete counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…§ Notably, it has been suggested that athletes experience improved postoperative outcomes compared with nonathletes. 36 However, as the previous literature has mainly focused on the male population, the primary aim of the present study was to (1) compare the PROs and satisfaction of athletic versus nonathletic female patients undergoing hip arthroscopic surgery for FAIS and (2) determine the return-to-sports rate and time to return to sports in female athletes. We hypothesized that female athletes would experience better outcomes than their nonathlete counterparts and that female athletes would have a high rate of return to sports.…”
mentioning
confidence: 99%
“…Then, osteochondroplasty is performed as described previously. 11 In patients with associated hip dysplasia or instability, a shoelace capsular plication should be also performed to provide soft tissue stability. This last one should be performed as previously described using UltraTape (Smith & Nephew) ( Fig 3 E).…”
Section: Surgical Techniquementioning
confidence: 99%
“…In phase 3, endurance strengthening was commenced only after ROM was maximized and after good stability in gait and movement was demonstrated. Patients were allowed to progress their physical activity only after passive ROM was symmetric and pain free, and they demonstrated a normal gait pattern [22].…”
Section: Rehabilitation Protocolmentioning
confidence: 99%